The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7717/peerj.9237
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring extensibility differences among elite adolescent and young dancers of different dance styles and non-dancers

Abstract: Background Hamstrings have been analyzed extensively due to their tendency to shorten and their effect in the lumbo-pelvic dynamics and the sagittal position of the spine in trunk flexion with extended knees positions. It has been demonstrated that practicing a certain sport results in long-term changes in hamstring extensibility. Despite this, adequate extensibility of the hamstring musculature is essential for the dancer’s performance. Several studies have found differences in the extensibility of the hamstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…These results are in line with other studies that have analyzed flexibility and range of motion (ROM) comparing between sexes [ 32 , 42 ]. Flexibility test performance has also been associated in the literature with age, finding that flexibility increases with advancing age, perhaps due to the susceptibility to improvement with training [ 32 , 43 ]. However, in the present study, no influence of age was observed in the differences found.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with other studies that have analyzed flexibility and range of motion (ROM) comparing between sexes [ 32 , 42 ]. Flexibility test performance has also been associated in the literature with age, finding that flexibility increases with advancing age, perhaps due to the susceptibility to improvement with training [ 32 , 43 ]. However, in the present study, no influence of age was observed in the differences found.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, previous studies have already pointed out that there might be differences in all physical tests that depend on cardiorespiratory endurance, muscle strength, muscle endurance, muscle power, speed, balance, coordination, accuracy, and agility between active and sedentary subjects, but not in tests that depend on flexibility [ 9 , 60 ]. This could be because the practice of regular physical activity increases muscular fitness and cardiorespiratory fitness in adolescents [ 76 , 77 ], but flexibility requires a high volume of stretching for range of motion to improve, which is not common in most sports practices [ 78 ]. In addition, a significant finding of our study was that only cardiorespiratory fitness showed itself to be a primary outcome to distinguish between active and sedentary individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Such excessive overtraining of extensor mechanisms may lead to patellofemoral syndrome, patellar tendinitis, or patellar tendon enthesopathy ( 6 ). Also, dancers’ posterior femoral muscles (muscles of the hamstring group) remain tense ( 39 ) as a necessity for proper shock absorption, and the continuous load affecting the extensor mechanism makes the knee joint one of the most loaded joints.…”
Section: Discussionmentioning
confidence: 99%